Cities : citizens & civilizations - Macdonald, Fiona (New York : Franklin Watts, 1992)
Describes the development of cities, from the early agricultural centers in the Fertile Crescent to modern metropolises in industrialized countries.
The first cities -- Ancient Egypt -- Greek city-states -- Imperial Rome -- Viking Hedeby -- Early America -- Cordoba -- Paris -- Venice and K'aifeng -- Florence -- Nuremberg -- Constantinople -- Amsterdam -- Vienna -- St. Petersburg -- Paris -- New York grows -- Industrial cities -- London expands -- London works -- Out of town -- Inner city -- Cityscapes -- Future cities -- Timeline.
Includes index and glossary.
7.5
5-8
Keywords: Cities and towns -- Forecasting -- Juvenile literature; Cities and towns -- History -- Juvenile literature; Extinct cities -- Juvenile literature; Cities and towns -- History; Cities and towns -- History; Extinct cities